Requirements for Utilizing Social Innovation as an Approach to Developing Human Capital in Saudi Society - Soliman, Manal; Ibrahim, Neveen; Hasanin, Takwa; Shamrokh, Mervat; Eldiasty, Ali; Abou El-Ela, Tarek; Abd Elhammid, Shaimaa S.; Helal, Ibrahim (European Journal of Sustainable Development, 2025)
This study explores the critical role of social innovation in enhancing human capital development within youth-focused organizations in Saudi Arabia. Aimed at identifying the necessary requirements for utilizing social innovation, the research adopts a descriptive approach, employing a comprehensive questionnaire to gather data from 352 employees and board members across eight youth institutions. Key findings reveal that the most significant requirements for fostering social innovation include continuous knowledge updating, the development of innovative problem-solving skills, and the cultivation of experience in creative task completion. Additionally, the study highlights the challenges faced by these institutions, such as insufficient technological resources, a lack of training programs, and resistance to change. The findings underline the importance of leveraging social innovation to improve organizational performance, promote creativity, and enhance employee job satisfaction. This research is particularly relevant to youth organizations seeking to innovate and build human capital to address emerging societal challenges. By integrating social innovation strategies, these organizations can more effectively meet the evolving needs of the youth they serve, contributing to broader community development goals. Keywords: social innovation, human capital development, youth institutions